Neurophysiological and clinical evaluation in patients with diabetes mellitus - Portillo, Roberto (2005)
Abstract Objective: To determine diabetic patients’ clinical and neurophysiological characteristics and correlate variables. Material and Methods: Fifty diabetes mellitus patients were studied at Guillermo Almenara National Hospital. Age, sex, occupation, length of disease, glycaemia, diet, treatment, sensorial symptoms, motor (SMNC) and sensorial (SMNC) nerve conduction speed of 12 nerves by patient, total 600 nerves, and prevalence of diabetic neuropathy (DN) were determined as well as the relation of the diverse variables with DN. Results: Ninety per cent of patients presented compromise, 86% fulfilled DN criteria; age was 38 to 78 years old (mean=58,5 years), 36 were males (72%), average time of disease was 89 months, glycaemia was 143 mg/dL, 74% received hypoglycaemic diet, 48% referred sensorial symptoms. There was no relation between DN and length of disease, glycaemia, treatment or sensorial symptoms. Conclusions: Exhaustive anamnesis to diabetic patients found 48% with DN suggestive symptoms, 86% presented neurophysiological findings compatible with DN; early detection of diabetes mellitus is important in order to avoid DN-like complications.